WACANA SOLIDARITAS DAN KEMAJEMUKAN ISLAM INDONESIA DI TENGAH PANDEMI COVID-19 - Luqman Al Hakim; Muhammad Faiz (Al'Adalah, 2020)
Covid-19 pandemic has demolished human activities, in period Covid 19 Indonesian Moslems being testing to inside solidarity and plurality. Because that has two choices to  Indonesian Moslems united and separated. Plurality and solidarity are very constructing remember for many Indonesian elements of Islam an example; MUI, NU, Muhammadiyah, etc. The role of government and preacher is big sake to lose Covid 19 misery. This research aims to look at how is the development of Moslems solidarity and plurality in the middle Covid 19, with a mapping to what extent impact solidarity and plurality are presenting from Indonesian Moslems. The research method used is qualitative, have as base Social observation, the result of this research Islamic concept solidarity and voluntary did Moeslems activities from the big Indonesian Islamic organizations with from any Islamic insantion. But in other that have present Islam be deliberate solidarity and plurality in the time Covid 19. Importantly to Indonesian Moeslems for mutual supporting and giving real actions in support concept solidarity and plurality sake together benefit.